THE INFLUENCE OF LEARNING OUTCOMES ON NISAIYYAH SUBJECTSLIFE SKILL CLASS 6 STUDENTS AT MODERN PONDOK ISLAM ASSALAM AJARAN 2021-2022 - Yusron Hanafi; Budi Sunariyanto (LPPM STAI Muhammadiyah Probolinggo, 2024)
This research is quantitative associative field research. There were 100 6th grade female students as the population of this study. 100 people were the sample. Sampling is determined bySatisfied Random Sampling. The method used is the data collection method (institutional documents) and the questionnaire method with questionnaires, while the analysis method uses IBM SPSS version 20.0 (statistics 20 license authorization wizard). From the results of research conducted by researchers, it can be concluded that: (1 The Nisaiyyah learning outcomes of grade 6 female students are good as indicated by an average score of 66.29. (2 The life skills scores of grade 6 female students are good which is indicated by an average value of 62.62. (3 There is no strong influence between Nisaiyyah learning outcomes on the life skills of class 6 CLASS 6 female students as determined by the results of the t test, the researcher obtained the results